Modified lio.5feo4 lithium supplement and preparation thereof and application thereof in lithium ion batteries

By coating and sintering Li5FeO4 with a metal M complex, a composite layer of metal M oxide and carbon is formed, which solves the problems of air stability and lithium compensation of Li5FeO4, and improves lithium compensation capacity and battery performance.

CN119864420BActive Publication Date: 2025-11-21CENT SOUTH UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510057635.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-11-21
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

Existing Li5FeO4 lithium supplements have problems in terms of air stability, low electronic conductivity and insufficient lithium compensation capacity. Existing coating structures are cumbersome and increase the interfacial impedance of the material.

Method used

Li5FeO4 was coated and sintered using metal M complexes to form a composite layer of metal M oxides and carbon. Citric acid and its salts or gluconic acid and its salts were used as complexing agents to optimize the structure and interface characteristics of the coating layer.

Benefits of technology

It significantly stimulates anion oxidation reaction, improves lithium replenishment capacity, enhances air stability and long-range cycling performance, and reduces interfacial impedance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864420B_ABST
    Figure CN119864420B_ABST
Patent Text Reader

Abstract

The application belongs to the field of lithium ion battery materials, and specifically discloses a modified Li5FeO4 lithium supplement agent, a preparation method and application thereof; the preparation method is as follows: after Li5FeO4 and a metal M complex are mixed, the mixture is sintered in a protective atmosphere to obtain a modified Li5FeO4 lithium supplement agent with a metal M oxide / C composite material coated on the surface of the Li5FeO4 in situ; the metal M complex is a complex formed by a metal M and a complexing agent, wherein the complexing agent comprises at least one of citric acid and a salt thereof and gluconic acid and a salt thereof; and the metal M comprises Ni and / or Co. The lithium ion positive electrode lithium supplement material provided by the application has excellent air stability, can stimulate anion redox reaction, promote Li ion release, and improve lithium ion compensation capacity, so that the lithium ion positive electrode lithium supplement material can be used as a high-energy-density positive electrode lithium supplement material which is simple to prepare and convenient to store, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the field of lithium ion batteries, and particularly relates to a lithium ion battery lithium supplementing agent. BACKGROUND

[0002] Lithium ion batteries (LIB) are currently the most promising and fastest developing high-efficiency secondary batteries, and have many advantages such as higher specific energy, lower self-discharge, good cycle performance, and no memory effect.

[0003] Li + All come from the positive electrode material, and the negative electrode generally uses graphite material. When the battery is charged for the first time, the surface of the negative electrode of the lithium ion battery will consume Li + to form a layer of SEI film, causing the initial capacity loss (ICL) problem, and the ICL of the lithium ion battery with a graphite negative electrode is about 7% to 10%. High-capacity silicon negative electrode materials are gradually applied to lithium ion batteries, but the ICL of the silicon negative electrode is as high as 50% to 70%. Therefore, it is of great significance to develop a simple and efficient lithium supplementing technology.

[0004] In recent years, researchers at home and abroad have gradually focused on positive electrode lithium supplementing. Positive electrode lithium supplementing is to select a positive electrode material with high lithium content outside the traditional positive electrode material, mix it with the traditional positive electrode material according to a certain proportion, and use it as a new positive electrode material for battery assembly. In the process of the first charge and discharge, the excess Li + released by the positive electrode material with high lithium content as an additive will fill the irreversible Li + loss generated in the cathode, thereby reducing the ICL of the entire battery.

[0005] Li5FeO4, as an ideal positive electrode lithium supplementing material, has a unique inverse fluorite structure, which is beneficial to the embedding and extraction of lithium ions, thereby improving its lithium supplementing performance. It has a very high specific capacity, which can reach 867 mAh / g. Its first delithiation specific capacity is 667.6 mAh / g. However, compared with other types of lithium supplementing agents, it still faces more prominent problems such as air stability, low electronic conductivity, and insufficient lithium compensation capacity.

[0006] To address the problems faced by Li5FeO4 lithium replenishers, existing technologies have provided some coating modification methods. For example, Chinese patent document CN111725576A discloses a carbon-coated lithium-rich oxide composite material and its preparation method. Chinese patent document CN112490415A discloses a lithium-ion cathode material lithium replenishing additive and its preparation method. The lithium replenishing additive includes a Li5FeO4 matrix and a coating layer on the surface of the Li5FeO4 matrix; the coating layer includes a first coating carbon layer on the surface of the Li5FeO4 matrix and a second coating transition metal oxide layer on the surface of the first coating layer. Furthermore, Chinese patent document CN113328079A discloses a cathode lithium replenishing material and a lithium-ion battery including the material, specifically describing a scheme using zirconium dioxide and boron oxide to coat the surface of Li5FeO4. Chinese patent document CN117438581A discloses a double-coated LiFeO lithium supplement, which includes a core-shell structure consisting of a core and a double-coated shell. The double-coated shell includes a first shell and a second shell, with the first shell located between the core and the second shell. The core is made of Li5FeO4, the first shell is made of a rare metal oxide layer, and the second shell is made of an organic polymer layer.

[0007] As can be seen, existing technologies disclose some schemes for coating Li5FeO4 with metal oxides and carbon. However, most of the existing metal oxides require rare metals. In addition, the existing coating structures and methods are relatively complicated. For example, many require multi-layer composites, which increases the preparation process. Furthermore, it also increases the material interface between the encapsulation layers, increasing impedance. At the same time, during the material charging process, the oxidation reaction of some oxygen anions or oxygen derivatives of Li5FeO4 is insufficient, which affects its lithium compensation, air stability and long-range cycling performance. Summary of the Invention

[0008] To address the problems of existing Li5FeO4 lithium supplements, this invention provides a method for preparing a modified Li5FeO4 lithium supplement, which aims to promote more anion oxidation reactions, participate in the charge compensation process, improve lithium supplementation capacity, and enhance air stability.

[0009] The second objective of this invention is to provide a modified Li5FeO4 lithium supplement prepared by the aforementioned method and its application.

[0010] A third objective of this invention is to provide a lithium-ion battery comprising the modified Li5FeO4 lithium supplementer, as well as its positive electrode and positive electrode active material.

[0011] A method for preparing a modified Li5FeO4 lithium supplement involves mixing Li5FeO4 and a metal M complex and then sintering the mixture in a protective atmosphere to obtain a modified Li5FeO4 lithium supplement with an in-situ coating of a metal M oxide / C composite material on the surface of Li5FeO4.

[0012] The metal M complex is a complex formed by metal M and a complexing agent, wherein the complexing agent includes at least one of citric acid and its salt, gluconic acid and its salt; wherein the metal M comprises Ni and / or Co.

[0013] This invention innovatively employs a metal M complex, which promotes the oxidation reaction of oxygen anions, to coat Li5FeO4 and then performs a single-stage sintering. This forms a composite coating layer of metal M oxide and carbon in Li5FeO4, and the material prepared by this method exhibits good surface uniformity and low interfacial impedance between the coating layer and the bulk phase. Research in this invention shows that the material prepared by this method can unexpectedly and significantly stimulate anion redox reactions, improve lithium replenishment capacity, and enhance air stability.

[0014] In this invention, the Li5FeO4 can be prepared by known means, for example, by calcining a mixed raw material containing a lithium source and an iron source.

[0015] In this invention, the lithium source is at least one of Li2O, Li2CO3, LiF, Li3PO4, and Li2C2O4.

[0016] In this invention, the Fe source is at least one of Fe2O3, Fe3O4, iron powder, and FeC2O4.

[0017] In this invention, the molar ratio of Li:Fe in the lithium source and iron source is 4.5~9.5:1, and can be further 5~6:1.

[0018] In this invention, the mixed raw materials also contain surfactants.

[0019] In this invention, the amount of surfactant added is 2 to 10 wt% of the iron source.

[0020] In this invention, the calcination temperature is 600-900℃; more specifically, it can be 750-850℃.

[0021] In this invention, the calcination time is 8-12 hours.

[0022] In this invention, the metal M complex includes at least one of nickel citrate, cobalt citrate, nickel gluconate, and cobalt gluconate.

[0023] In this invention, the complexing agent may be citric acid, gluconic acid, or their sodium, potassium, or ammonium salts.

[0024] Preferably, in the metal M complex, the metal M comprises nickel and cobalt in a molar ratio of 1:0.5~2.

[0025] Preferably, in the metal M complex, the complexing agent includes citric acid and its salt, and also includes gluconic acid and its salt.

[0026] The present invention demonstrates that, under the innovative coating of the aforementioned metal M complex, further employing a nickel-cobalt combined metal and / or the aforementioned citric acid-gluconic acid combined complex structure can achieve the interaction between the two, further enhance the surface structure, optimize interface characteristics, and further synergistically improve the coating effect.

[0027] In this invention, the molar ratio of M / Fe in the metal M complex and Li5FeO4 is 0.01~0.1:1; more specifically, it can be 0.03~0.09:1.

[0028] In this invention, the sintering temperature is 300~600℃; more specifically, it can be 350~550℃.

[0029] Preferably, the sintering time is 1 to 6 hours, and more preferably 2 to 3 hours.

[0030] The present invention also provides a modified Li5FeO4 lithium supplement prepared by the preparation method described above.

[0031] The preparation method described in this invention can unexpectedly form a composite layer of metal M oxide and carbon in situ within Li5FeO4, and can optimize the structure and morphology of the coating layer, as well as its composite effect with the bulk phase. The modified Li5FeO4 lithium supplement prepared by the method described in this invention exhibits improved capacity, air stability, and long-range cycling stability.

[0032] The present invention also provides the application of the modified Li5FeO4 lithium supplement as a lithium supplement in the preparation of lithium-ion batteries;

[0033] Preferably, it is used to prepare the positive electrode of a lithium-ion battery;

[0034] Preferably, it is used to prepare the positive electrode material for lithium-ion batteries.

[0035] In this invention, lithium-ion batteries and their associated components and materials can be prepared by using the modified Li5FeO4 lithium supplementer based on existing materials, equipment and principles.

[0036] The present invention also provides a lithium-ion battery lithium replenishing positive electrode active material, comprising a positive electrode active material and the modified Li5FeO4 lithium replenishing agent.

[0037] The positive electrode active material can be a conventional positive electrode active material.

[0038] Preferably, the positive electrode active material is at least one of LiCoO2, LiFePO4, and NCM ternary materials;

[0039] Preferably, the modified Li5FeO4 lithium supplement has a weight percentage of 2-15%; more preferably 5-10%. Studies have found that controlling the modified Li5FeO4 lithium supplement within the above range can further enhance the performance of the additive, further improve the electrical performance, and improve the first charge-discharge coulombic efficiency.

[0040] In this invention, the lithium-supplementing cathode material includes the lithium-supplementing cathode active material, and may also include conductive agents, binders, and other components.

[0041] The conductive agent can be any conductive material known in the industry that can be used in the positive electrode; for example, at least one of acetylene black and Ketjen black. The weight percentage of the conductive agent is 1-15%; preferably 5-10%.

[0042] The binder can be any material known in the industry that can be used to bond the positive electrode components together; for example, it can be at least one of PVDF and PTFE. The weight percentage of the binder is 1-15%; preferably 5-10%.

[0043] A lithium-supplemented cathode includes a current collector and a cathode material composited on its surface, wherein the cathode material is the lithium-supplemented cathode material.

[0044] The present invention also provides a lithium-ion battery comprising the modified Li5FeO4 lithium replenishing agent described in the present invention; preferably, it comprises the lithium replenishing positive electrode active material, lithium replenishing positive electrode material, or lithium replenishing positive electrode.

[0045] In this invention, the lithium-ion battery, except for the positive electrode which contains the modified Li5FeO4 lithium replenishing agent described in this invention, can use other known components and materials. For example, the negative electrode active material is one or more of graphite, hard carbon, and silicon carbide.

[0046] The application of the aforementioned lithium-replenishing cathode material involves treating the assembled lithium-ion battery with lithium replenishment. Preferably, this treatment involves one charge-discharge cycle. The first charge uses a constant current or constant voltage charging rate of 0.02~0.1C, with a cutoff voltage of 4.0~4.5V. The first discharge uses a constant current discharge rate of 0.02~0.1C, with a cutoff voltage of 1.5~2.0V. Using a small current during charging allows for complete extraction of lithium from the material, while using a large current during discharging can disrupt the material structure, preventing lithium from returning to the battery.

[0047] As a general technical concept, the present invention also provides a lithium-ion battery assembled from the aforementioned lithium-ion cathode material. The initial charge-discharge coulombic efficiency of the lithium-ion battery is 90-99%.

[0048] Compared with the prior art, the advantages of the present invention are as follows:

[0049] This invention innovatively employs a metal M complex to encapsulate Li5FeO4 and performs a single-stage sintering, thereby forming a composite coating layer of metal M oxide and carbon in Li5FeO4. Furthermore, the material prepared by this method exhibits good surface uniformity and low interfacial impedance between the coating layer and the bulk phase. Research in this invention shows that the material prepared by this method can unexpectedly and significantly stimulate anionic oxidation reactions, participate in charge compensation, improve lithium replenishment capacity, and enhance air stability. Attached Figure Description

[0050] Figure 1 The first charge-discharge curve of Li5FeO4 is shown in Comparative Example 1.

[0051] Figure 2 The first charge-discharge curve of Li5FeO4 after modification in Example 1 is shown. Detailed Implementation

[0052] The Li5FeO4 described in this invention can be obtained from external purchases or prepared using existing methods. For example, in the following cases, the Li5FeO4 can be prepared on-site using the following steps:

[0053] A certain amount of Fe2O3 and Li2O were uniformly mixed at a Li:Fe molar ratio of 5.5. The uniformly mixed raw materials were heated to 800 °C in an argon atmosphere and held for 10 h to successfully prepare Li5FeO4.

[0054] Example 1

[0055] Weigh a certain proportion of Li5FeO4 and metal complex (nickel citrate in this case, where the Ni / Fe molar ratio is 0.04:1) and disperse them in NMP. After sonication for 1 hour, mechanical stirring for 4-6 hours is performed. The product generated by the reaction is then dried in a vacuum oven to obtain Li5FeO4@nickel citrate.

[0056] Modified Li5FeO4 was prepared by heating the dried ball-milled mixture at 400℃ for 2 hours under an Ar atmosphere.

[0057] Example 2:

[0058] Compared to Example 1, the only difference is that the type of metal complex is changed, for example:

[0059] Group A: The metal complex is cobalt citrate;

[0060] Group B: The metal complex is cobalt citrate and nickel citrate with a Co / Ni molar ratio of 1:1, wherein the total molar amount of Co / Ni is the same as in Example 1.

[0061] Group C: The molar ratio of nickel in the metal complex to Fe in Li5FeO4 is 0.08:1.

[0062] All other operations and parameters are the same as in Example 1.

[0063] Example 3:

[0064] Compared to Example 1, the only difference is that the type of metal complex is changed, specifically:

[0065] A: The metal complex is nickel gluconate, and the molar amount of nickel is the same as in Example 1;

[0066] B: The metal complex is nickel gluconate and nickel citrate, wherein nickel in nickel gluconate accounts for 50% of the total nickel molar amount, and the molar amount of nickel is the same as in Example 1;

[0067] All other operations and parameters are the same as in Example 1.

[0068] Example 4:

[0069] Compared to Example 1, the only difference is the change in the roasting process; the experimental groups are as follows:

[0070] Group A: The roasting time is 4 hours;

[0071] Group B: Calcination temperature is 500 ℃. Other operations and parameters are the same as in Example 1.

[0072] Comparative Example 1

[0073] Compared with Example 1, the only difference is that the coating modification of Example 1 was not performed, and the prepared Li5FeO4 was directly used as the lithium supplement.

[0074] Comparative Example 2

[0075] Compared with Example 1, the only difference is that Li5FeO4 and citric acid (with the same weight as the citrate ion in the iron citrate in Example 1) were first carbonized (carbonization temperature was 400°C and time was 2h) to obtain carbon-coated material. Then, it was mixed with nickel nitrate (the amount of nickel was the same as the amount of nickel in the metal complex in Example 1) and then calcined at 400°C for 2h to finally obtain modified Li5FeO4.

[0076] Comparative Example 3

[0077] Compared with Example 1, the only difference is that the calcination temperature is 800°C, while all other operations and parameters are the same as in Example 1.

[0078] Comparative Example 4

[0079] Compared with Example 1, the only difference is that the metal complex is copper citrate, and the weight of copper is the same as that of nickel in Example 1; all other operations and parameters are the same as in Example 1.

[0080] Comparative Example 5

[0081] Compared with Example 1, the only difference is that nickel acetate is used instead of nickel citrate, wherein the weight of nickel is the same as in Example 1; all other operations and parameters are the same as in Example 1.

[0082] The results of air stability and lithium replenishment capacity tests are shown in Table 1.

[0083]

[0084] Note: "0h" refers to materials that have not been exposed to air, such as newly prepared materials or materials that have been stored directly in an Ar atmosphere after being prepared. "Exposure for 24h" refers to materials stored for 24 hours under conditions of air and 50% humidity.

[0085] As can be seen from the examples and comparative examples, the present invention innovatively uses a metal M complex to encapsulate Li5FeO4 and perform a single-stage sintering, which can significantly stimulate the anion oxidation reaction, participate in charge compensation, improve lithium replenishment capacity, and improve air stability.

[0086] Furthermore, as demonstrated in Examples 1 and 2, the use of metal complexes combining nickel and cobalt, and / or metal complexes with gluconic acid and citric acid as dual complexes, can unexpectedly further optimize the interface structure, thereby further improving the lithium replenishment effect and air stability.

[0087] As can be seen from the embodiments and comparative examples described above, the technical solution of the present invention can effectively improve stability and improve its cycling stability under air conditions.

Claims

1. A method for preparing a modified Li5FeO4 lithium supplement, characterized in that, Li5FeO4 and a metal M complex were mixed and sintered in a protective atmosphere to obtain a modified Li5FeO4 lithium supplement with an in-situ coating of metal M oxide / C composite material on the surface of Li5FeO4; the sintering temperature was 300~600℃. The metal M complex is a complex formed by metal M and a complexing agent, wherein the complexing agent includes at least one of citric acid and its salt, gluconic acid and its salt; wherein the metal M comprises Ni and / or Co.

2. The preparation method of the modified Li5FeO4 lithium supplement as described in claim 1, characterized in that, The Li5FeO4 is obtained by calcining a mixture of raw materials containing lithium and iron sources.

3. The preparation method of the modified Li5FeO4 lithium supplement as described in claim 2, characterized in that, The lithium source is at least one of Li2O, Li2CO3, LiF, Li3PO4, and Li2C2O4.

4. The preparation method of the modified Li5FeO4 lithium supplement as described in claim 2, characterized in that, The Fe source is at least one of Fe2O3, Fe3O4, iron powder, and FeC2O4.

5. The preparation method of the modified Li5FeO4 lithium supplement as described in claim 2, characterized in that, The molar ratio of Li:Fe in the lithium and iron sources is 4.5~9.5:

1.

6. The method for preparing the modified Li5FeO4 lithium supplement as described in claim 2, characterized in that, The mixed raw materials also contain surfactants.

7. The preparation method of the modified Li5FeO4 lithium supplement as described in claim 6, characterized in that, The amount of surfactant added is 2 to 10 wt% of the iron source.

8. The method for preparing the modified Li5FeO4 lithium supplement as described in claim 2, characterized in that, The calcination temperature is 600–900℃.

9. The method for preparing the modified Li5FeO4 lithium supplement as described in claim 2, characterized in that, The calcination time is 6-12 h.

10. The method for preparing the modified Li5FeO4 lithium supplement as described in claim 1, characterized in that, In the aforementioned metal M complex, the metal M comprises nickel and cobalt in a molar ratio of 1:0.5~2.

11. The method for preparing the modified Li5FeO4 lithium supplement as described in claim 1, characterized in that, In the aforementioned metal M complex, the complexing agent includes citric acid and its salts, and also includes gluconic acid and its salts.

12. The method for preparing the modified Li5FeO4 lithium supplement as described in claim 1, characterized in that, The molar ratio of M / Fe in the metal M complex and Li5FeO4 is 0.01~0.1:

1.

13. The method for preparing the modified Li5FeO4 lithium supplement as described in claim 1, characterized in that, The sintering time is 1 to 6 hours.

14. A modified Li5FeO4 lithium supplement prepared by the preparation method according to any one of claims 1 to 13.

15. A lithium-supplementing positive electrode active material, comprising a positive electrode active material and a lithium-supplementing agent, characterized in that, The lithium replenishing agent includes the modified Li5FeO4 lithium replenishing agent prepared by the preparation method according to any one of claims 1 to 13.

16. The lithium-supplemented cathode active material as described in claim 15, characterized in that, The positive electrode active material is at least one of LiCoO2, LiFePO4, and NCM ternary materials.

17. The lithium-supplemented cathode active material as described in claim 15 or 16, characterized in that, In the lithium-supplementing positive electrode active material, the weight percentage of the lithium-supplementing agent is 2-15%.

18. The lithium-supplemented cathode active material as described in claim 17, characterized in that, In the lithium-supplementing positive electrode active material, the weight percentage of the lithium-supplementing agent is 5-10%.

19. A lithium-supplemented cathode material, characterized in that, It includes the lithium-supplemented positive electrode active material according to any one of claims 15 to 18.

20. The lithium-supplemented cathode material as described in claim 19, characterized in that, It also contains adhesives and conductive agents.

21. The lithium-supplemented cathode material as described in claim 20, characterized in that, The conductive agent includes at least one of acetylene black and Ketjen black; the binder includes at least one of PVDF and PTFE.

22. The lithium-supplemented cathode material as described in claim 20 or 21, characterized in that, The conductive agent has a weight percentage of 1-15%; The adhesive has a weight percentage of 1-15%.

23. The lithium-supplemented cathode material as described in claim 22, characterized in that, The conductive agent has a weight percentage of 5-10%; The adhesive has a weight percentage of 5-10%.

24. A lithium-ion cathode, comprising a current collector and a cathode material composited thereon, characterized in that, The cathode material is the lithium-supplemented cathode material according to any one of claims 19 to 23.

25. A lithium-ion battery with lithium replenishment, characterized in that, It includes the lithium-filled cathode as described in claim 24.

Citation Information

Patent Citations

  • Carbon-coated lithium-rich oxide composite material and preparation method thereof

    CN111725576A

  • Positive electrode lithium supplementing material and lithium ion battery comprising same

    CN113328079A

  • Double-coated Li5FeO4 lithium supplement agent and preparation method thereof

    CN117438581A

  • Lithium supplement additive for lithium ion cathode material and preparation method thereof

    CN112490415A

  • Ultrahigh-lithium-content material and lithium self-supplementing composite positive electrode material

    CN114927777A